Molecular Diagnostics. (April 2015) - Choe, Hyonmin; Deirmengian, Carl A.; Hickok, Noreen J.; Morrison, Tiffany N.; Tuan, Rocky S.
Abstract : Orthopaedic infections are complex conditions that require immediate diagnosis and accurate identification of the causative organisms to facilitate appropriate management. Conventional methodologies for diagnosis of these infections sometimes lack accuracy or sufficient rapidity. Molecular diagnostics is an emerging area of bench-to-bedside research in orthopaedic infections. Examples of promising molecular diagnostics include measurement of a specific biomarker in the synovial fluid, polymerase chain reaction–based detection of bacterial genes, and metabolomic determination of responses to orthopaedic infection.